Tunicothrix halophila n. sp., a Secondarily Oligomerized Parabirojimid Hypotrich (Ciliophora, Spirotrichea) From Hypersaline Costal Water in Korea - Omar, Atef; Moon, Ji Hye; Nam, Seung Won; Jung, Jae-Ho (Frontiers in Microbiology, 2021)
Tunicothrix halophila n. sp. was discovered in a hypersaline marine sample from Jeju Island, Korea. It is characterized by the highly reduced number of dorsal bristles. In addition, the main character of the genus Tunicothrix (e.g., alveolar layer) is absent/indistinct. To figure out its identity and phylogenetic relationship, we examined the new species based on modern morphological methods and molecular phylogenetic analyses. Since the parabirojimids are of basal position to core hypotrichs and a smaller data set could show incorrect phylogenetic relationships among the hypotrichs, we used a huge data set composed of 1,460 DNA sequences to infer the phylogenetic tree. The reduction of dorsal bristles is very likely a secondarily evolved character in hypotrichs, resulting in the independent phenotypic adaptation in the hypersaline ecosystems as shown in other hypersaline hypotrichs. Furthermore, the so-called right marginal row 1 in other congeners is found to produce a pretransverse and a transverse cirrus and thus we recommend using the term frontoventral row. Based on our data, we can justify Tunicothrix halophila n. sp. as a new species, however, despite the phenotypic distinctiveness, we refrain to establish a new genus because of the missing data and the non-monophyly of Tunicothrix.